Goverment Management Transformation in Bandung Regency West Java, Indonesia (A Study at Department of Education and Culture) - Dede Sri Kartini (Jurnal Ilmu Pemerintahan Widya Praja, 2017)
Transformation is a transtition process from a certain period to the next phase, which happens due to the presence of innovation or alteration, wheter in structural or prosedural aspects, planned or unplanned. “ Basically, transformation is a continous process. It includes reframing, resructuring, revitalization and renewal. Bandung regency had held regional general elections (Pilkada) in 2015, and already transformed its goverment management, Eventough the Regent himself, as incumbent usually faces difficulties to implement transformation inside his burreucracy system. By using qualitative and descriptive method, the researcers had interviewed the Regent of Bandung, Chief of Bappeda (Regional Development Planning Agency), Chief of Department of Education and Non Govermental Organizations in Education sector. The result of this research described that in reframing aspects, the education system have been altering from the current progress, not only depended on Startegic Planning , but also acomodated new ideas to encourage the success of educational programs. Meanwhile, for recruiting aspects, the goverments found difficulties since the regulations  from the National Goverment was not suitable within the needs in Bandung Regency. The revitalization aspects cannot be implemented yet, eventhough the Chief of Educations has already figure up the problem, such as the importance in buid Vocational School in Agriculture and Animal Husbandry. For renewal aspects, the goverment established “Edu Share” to socialize , facilitate and distribute scholarsips , and Doctorates Forum in Bandung Regency. Eventough the institutions is build outside the autority of Department of Education. The researchers concluded that , the shape of transformation in goverment management, especially in educational aspect has been dominated by the rules, whom did not able to adapt into the surrounding area, especially in Bandung Regency. Based on this condition, it is highly recommended, for the Chief of Education to be able to create activites which is consistent with the current rules, but also be able to satisfy the needs of society.Keywords: Reframing, Restructuring, Revitalizations, Renewal